Proof of Predicate Crime as a Basis for Prosecution of Money Laundering Crimes - Rika Kurniasari Abdulgani (International Journal of Science and Society, 2022)
Money laundering is an act that is passed on from the original criminal act (follow-up crime). In Indonesia, the criminalization of money laundering is realized by Law Number 8 of 2010 concerning the Prevention and Eradication of Money Laundering Crimes, which repeals Law Number 15 of 2002. Article 69 of Law Number 8 of 2010 explains that "it is not mandatory to prove in advance the original criminal act." This provision adopts a reversal of the burden of proof and the seizure of civil assets. This makes a difference, where money laundering is a follow-up crime, in line with the theory of "no money laundering without core crime." Proven predicate crimes can be considered for money laundering. In some court rulings, the panel of judges relied on proving a predicate crime to prove money laundering. So that the element of wealth that is reasonably suspected to be the result of a criminal act can be proven. Therefore, it is necessary to conduct an assessment of (1). What are the implications of not proving predicate crime in the judicial process of money laundering? (2). How does the predicate crime act's implementation affect the criminal justice process of money laundering?